The Double-Edged Sword of Popularization: The Role of Science Communication Research in the Popsci.com Comment Shutoff. (October 2015) - Walsh, Lynda
The decision byPopsci.com editors to shut off public comments in 2013 surprised many scholars of science journalism—particularly since the decision was justified in large part by reference to science communication scholarship. This commentary engages in a rhetorical analysis of the events surrounding the decision—in particular, the popularization of Anderson et al. (2014), the editorial stance atPopsci.com, and the content of blog comments leading up to the shutoff—to better appreciate what led to the foreclosure of a significant forum for protodeliberation on science research and policy.